Process evaluation and cost analysis of the team approach in diabetes management in a primary care setting - Salleh, Zul Azrizal (2023)
Introduction: The Team Approach is a patient-centred multidisciplinary approach in the management of diabetes that aims to empower patients in the self-care towards achieving good diabetes control. This study began with the development of the flow chart and clinical pathway of the Team Approach that guided the process evaluation and cost analysis of the program and the additional costs that required to improve the program. Methodology: This study consisted of three parts. Part 1 of the study is the design and development of a flow chart and clinical pathway that was developed from observing the work processes and activities of the Team Approach at the Simpang Kuala health clinic. The development of the flow chart and clinical pathway was based on the 10- step framework for developing and disseminating clinical pathway by the Centre of Evidence-based Practice, University of Pennsylvania Health System, Philadelphia. Part 2 was a process evaluation of the Team Approach on the program’s context, reach, dose delivered, fidelity, and implementation. Part 3 of the research was a cost analysis of the Team Approach using the top-down and bottom-up costing approach to determine the cost per patient from providers’ perspective. Additional resources and costs required to expand the program to achieve 50% and 70% of patients with HbA1c level ≤6.5% was also forecasted. Result: The Diabetes Patient Process Flow Chart (DPPF) and the Integrated Care Pathway of Diabetes Management (ICPDM) of the Team Approach work processes were visualized using the Business Process Model and Notation tool and the time-task matrix format of a chain model. The process evaluation discovered factors that influenced the implementation of Team Approach was the leadership of the clinic’s manager, human resource, facilities and equipment, health informatics, variations in consultation practices, commitments of patients, acceptance of new knowledge, stigma on insulin use and the effect of Covid-19 pandemic. The scores obtained in the evaluation of reach, dose delivered and fidelity of the services and consultations in the Team Approach ranged from 0% to 100%. The overall score for the implementation of the Team Approach in diabetes management and care was 57%. The cost of treatment for diabetes patient in 2020 was RM1,330.05 per patient. To achieve 50% and 70% of the total diabetes patients with HbA1c of ≤6.5% in the same year, the cost per patient will be RM1,659.34 and RM2,117.68 respectively. Conclusion: The research is a comprehensive study of the Team Approach in diabetes management in a primary care setting. The flow chart and clinical pathway will be useful in standardizing the delivery of care and sharing of practices among other clinics. Whilst the process evaluation enabled the weaknesses of the program to be identified, thus aiding future improvements and guiding the Ministry of Health in the planning resources and funding for the management and care of diabetes mellitus in Malaysia.